Was a Mobile Health Strategy One of Your New Year’s Resolutions? - Felkey, Bill G. (Thomas Land Publishers, Inc., 2014)
Culture change is hard in any organization. However, it can often lead to positive results. We believe that the culture of health care needs to focus on how mobile health tools can assist in care provision in hospitals and health systems. In this installment, we explore some of the steps necessary to help move mobile health into the mainstream of health care.